2015
DOI: 10.1111/apa.12852
|View full text |Cite
|
Sign up to set email alerts
|

Occult bacteraemia is uncommon in febrile infants who appear well, and close clinical follow-up is more appropriate than blood tests

Abstract: In the era of the 13-valent pneumococcal conjugated vaccine, occult bacteraemia is an uncommon event in febrile children aged three to 36 who otherwise appear well and close follow-up should replace blood analysis in such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In a retrospective case series of all blood cultures obtained between 1998 and 2003 in northern California outpatient clinics and emergency departments from previously healthy children three to 36 months old, Herz et al showed that leukocytosis >15,000/mm 3 is a poor predictor of bacteremia in febrile toddlers (positive predictive value of 1.50%) and in children routinely immunized with PCV7 [ 15 ]. Hernandez-Bou [ 33 ] showed recently, in 591 children aged three to 36 months vaccinated with PCV13 in a tertiary-care medical center in Spain, that an elevated band count was the best predictor of the uncommon (six patients only, 1.0%) cases of OB that were diagnosed, with 66.70% sensitivity and 93.30% specificity, while the positive predictive values of a WBC count >15,000/mm 3 , C-reactive protein >40 mg/L and procalcitonin >0.5 ng/mL were low. It is clear, today, taking into consideration the low rates of OB in patients vaccinated with PCVs, that use of the white blood cell count alone to guide the empiric use of antibiotics is not indicated anymore, and that new guidelines advocating for a management change are needed in the approach to the previously healthy febrile toddler [ 7 , 8 , 16 , 20 , 28 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective case series of all blood cultures obtained between 1998 and 2003 in northern California outpatient clinics and emergency departments from previously healthy children three to 36 months old, Herz et al showed that leukocytosis >15,000/mm 3 is a poor predictor of bacteremia in febrile toddlers (positive predictive value of 1.50%) and in children routinely immunized with PCV7 [ 15 ]. Hernandez-Bou [ 33 ] showed recently, in 591 children aged three to 36 months vaccinated with PCV13 in a tertiary-care medical center in Spain, that an elevated band count was the best predictor of the uncommon (six patients only, 1.0%) cases of OB that were diagnosed, with 66.70% sensitivity and 93.30% specificity, while the positive predictive values of a WBC count >15,000/mm 3 , C-reactive protein >40 mg/L and procalcitonin >0.5 ng/mL were low. It is clear, today, taking into consideration the low rates of OB in patients vaccinated with PCVs, that use of the white blood cell count alone to guide the empiric use of antibiotics is not indicated anymore, and that new guidelines advocating for a management change are needed in the approach to the previously healthy febrile toddler [ 7 , 8 , 16 , 20 , 28 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with occult bacteremia had higher mean temperature (40.2 C ± 0.5 C) when compared with patients with negative or contaminated cultures (p value < 0.001) [31]. The introduction of the heptavalent pneumococcal conjugate vaccine (PCV7) led to further declines in the overall rates of occult bacteremia to <0.5-1% [83,84].…”
Section: Occult Bacteremiamentioning
confidence: 99%
“…Occult bacteremia may represent a lag in the clinical manifestation of the disease, and this has been documented in various studies [83][84][85][86]. It is difficult to ascertain the seriousness of occult bacteremia, but biomarkers such as neutrophil count, CRP and PCT are useful analytical parameters [84,85].…”
Section: Occult Bacteremiamentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical characteristics of these patients, including age, sex, onset of fever, temperature, and white blood cell counts, were comparable to those of patients in other studies reporting FWS among children aged 3 to 36 months in Asia 12 and Europe. 13-15 One major issue in this study was the immunization status of the enrolled children. We obtained an immunization history for 60 patients (90%); all of them had received only the basic immunizations included in Thailand’s national immunization schedule according to their ages, except the PCV and Hib vaccine.…”
Section: Discussionmentioning
confidence: 99%